Effectiveness of Jakarta Kini Application in Improving Information System for Public Services in 2024 - Tri Wulandari; Alya Azzahraa Jashilka Zahlianti; Neysa Shabrina Riandini; Allina Ramadhina; Abdul Rahman (Public Policy : Jurnal Aplikasi Kebijakan Publik dan Bisnis, 2025)
This study examines the effectiveness of the Jakarta Kini (JAKI) application in improving Jakarta’s public service information system. Using a quantitative approach, data from 100 respondents were analyzed through validity, reliability, and regression tests in SPSS. Effectiveness was measured by five indicators from Campbell’s theory and four indicators from the public service information system framework. Results show that JAKI’s effectiveness significantly enhances public service information quality. The study highlights digital innovation’s role in improving service delivery, transparency, and user engagement, and offers practical recommendations for advancing JAKI and similar smart city applications.